Ghrelin binding to serum albumin and its biological impact. (15th November 2016) - Lufrano, Daniela; Trejo, Sebastián A.; Llovera, Ramiro E.; Salgueiro, Mariano; Fernandez, Gimena; Martínez Damonte, Valentina; González Flecha, F. Luis; Raingo, Jesica; Ermácora, Mario R.; Perelló, Mario
Abstract: Ghrelin is an octanoylated peptide hormone that plays a key role in the regulation of the body weight and glucose homeostasis. In plasma, ghrelin circulates bound to larger proteins whose identities are partially established. Here, we used size exclusion chromatography, mass spectrometry and isothermal titration microcalorimetry to show that ghrelin interacts with serum albumin. Furthermore, we found that such interaction displays an estimated dissociation constant ( K D ) in the micromolar range and involves albumin fatty-acid binding sites as well as the octanoyl moiety of ghrelin. Notably, albumin-ghrelin interaction reduces the spontaneous deacylation of the hormone. Both in vitro experiments—assessing ghrelin ability to inhibit calcium channels—and in vivo studies—evaluating ghrelin orexigenic effects—indicate that the binding to albumin affects the bioactivity of the hormone. In conclusion, our results suggest that ghrelin binds to serum albumin and that this interaction impacts on the biological activity of the hormone. Highlights: Ghrelin interacts with serum albumin with significant affinity ( K D = 4.6 × 10 −6 M). The interaction involves albumin fatty-acid binding sites and ghrelin octanoyl moiety. Albumin-ghrelin interaction reduces the spontaneous deacylation of the hormone. Binding to albumin impairs ghrelin biological activity.